Adsorption of coliphage on sand, soil, and floc - Sakchai Suddevgrai; Ohgaki, S.; Nguyen, Cong Thanh; Vigneswaran, S.; Chongrak Polprasert; German Academic Exchange (DAAD) Federal Republic of Germamy (Bangkok : Asian Institute of Technology, 1985)
A Coliphage (host Cill: E.Coli B) was isolated from klong Nueng, Rangsit, Thailand and used in this study on the removal of coliphage by sand, soil, and floc. The adsorption on sand and soil was investigated at different pH values in the presence and absence of monovalent and divalent cations. Sand (diameter: 0.43-0.50mm) was not effective in removing this king of coliphage. Increasing the amount of monovalent cation (Na+) up to 0.2 mole/1 could not improve the removal of the coliphage. However, the removal of the coliphage increased at pH 7.0 with increasing concentration of calcium or magnesium ions. Two kinds of acidic soil (paddy rice soil and lateritic soil having pH 3.4 and 4.5 respectively completely inactivated the coliphage sine the coliphage was sensitive to acidic medium. Mg(OH)2 precipitate formed at pH 11.0 removed coliphage upto 99.6% even though its concentration was as low as 0.002 mole/1. The coliphage which was adsorbed on Mg(OH)2 precipitate was extracted by adding organic matter like beef extract. Proteinaceous materials like beef extract hindered the adsorption and flocculation processes of the coliphage.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science, School of Environment, Resources and Development
Thesis (M.Sc.) - Asian Institute of Technology, 1985
Keywords: Sewage -- Purification -- Flocculation